RELIABILITY OF ORTHOPANTOMOGRAM IN COMPARISON TO LATERAL CEPHALOGRAM FOR LINEAR MANDIBULAR MEASUREMENTS - Asma Faryal; Attiya Shaikh (Journal of Ayub Medical College Abbottabad, 2022)
Background: Mandibular asymmetries are commonly seen as asymmetric traits among orthodontic and orthognathic patients which require bilateral mandibular assessment for diagnosis and treatment. An orthopantomogram can be used to measure and compare right and left sides of mandible. The objective of this study was to investigate the reliability of left and right sides of orthopantomogram for determining the linear mandibular measurements and to check whether these values are identical with the values of linear mandibular measurements determined from lateral cephalogram. Methods: Orthopantomogram and lateral cephalogram were taken from 118 patients of age group 12-35 years from Orthodontic department, Liaquat College of Medicine & Dentistry and Darul Sehat Hospital, Karachi, Pakistan. Linear mandibular measurements were detected and compared between orthopantomograms and lateral cephalograms. Right and the left sides of orthopantomograms were compared for all of the linear mandibular parameters by using paired t-test. Independent sample t-test was performed for the comparison between orthopantomogram and lateral cephalogram using SPSS version 26.0. Results: Statistically significant differences were observed when orthopantomograms were compared with lateral cephalograms for mandibular body length (p=0.000) and total mandibular length (p=0.000). No statistically significant difference was found between orthopantomograms and lateral cephalograms for ramus height (p=0.226, p=0.177). Neither any significant difference was observed between right and left sides of an orthopantomogram. Conclusion: An orthopantomogram can be used to evaluate vertical mandibular measurements as reliably as a lateral cephalogram. However, it is required for clinicians to be vigilant when determining horizontal mandibular measurements from orthopantomograms as they are unpredictable.